1999
DOI: 10.2169/internalmedicine.38.984
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoidosis Associated with Connective Tissue Diseases: Report of 3 Cases.

Abstract: Disease activity in Japanese sarcoidosis patients is generally mild. However, the pulmonary sarcoidosis coexisting with connective tissue disease is likely to be progressive. Wereport here three cases of sarcoidosis coexisting with connective tissue diseases, who developed pulmonary manifestations from stage II to stage III. (Internal Medicine 38: 984-987, 1999)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…31 A prospective study found only 4% of sarcoidosis patients developed CTD after 10 years. 32 However, only 1% of CTD patients followed up for 10 years were subsequently diagnosed with sarcoidosis, which seems to imply that sarcoidosis patients may be more likely to have features of CTD, but CTD patients may not be more likely to develop sarcoidosis. 33…”
Section: Connective Tissue Diseasementioning
confidence: 95%
“…31 A prospective study found only 4% of sarcoidosis patients developed CTD after 10 years. 32 However, only 1% of CTD patients followed up for 10 years were subsequently diagnosed with sarcoidosis, which seems to imply that sarcoidosis patients may be more likely to have features of CTD, but CTD patients may not be more likely to develop sarcoidosis. 33…”
Section: Connective Tissue Diseasementioning
confidence: 95%